2021
DOI: 10.1037/sah0000329
|View full text |Cite
|
Sign up to set email alerts
|

Mental illness, problem, disorder, distress: Does terminology matter when measuring stigma?

Abstract: It has become commonplace to adapt the terminology used to reference mental illness in stigma measures to avoid further stigmatizing people who have experienced a mental health problem. However, to our knowledge, no study has examined the effect of modifying terminology in stigma measures on levels of stigma endorsement or on the relationship between measured stigma and important outcomes. We surveyed 3,367 people with a current or past history of a mental illness using Amazon MTurk and randomly assigned them … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 38 publications
4
6
0
Order By: Relevance
“…Our findings indicate that laypeople do not meaningfully differentiate between several prominent labels and instead treat them as interchangeable. This conclusion is also compatible with the recent finding that alternative terms had little or no impact on stigma or the association between stigma and key outcomes [ 29 ].…”
Section: Discussionsupporting
confidence: 91%
“…Our findings indicate that laypeople do not meaningfully differentiate between several prominent labels and instead treat them as interchangeable. This conclusion is also compatible with the recent finding that alternative terms had little or no impact on stigma or the association between stigma and key outcomes [ 29 ].…”
Section: Discussionsupporting
confidence: 91%
“…However, this term could sound too severe or clinical for some, calling up stigma, and overlooking strengths and wellness. This finding resonates with other studies in the literature that have found the term mental illness to be associated with stigma, according to members of the general public (Fox et al, 2021;Granello & Gibbs, 2016). Our results in this area also link to other findings that suggest that mental illness is used most commonly by people with mental health problems (Fox et al, 2021).…”
Section: Mental Illnesssupporting
confidence: 92%
“…This finding resonates with other studies in the literature that have found the term mental illness to be associated with stigma, according to members of the general public (Fox et al, 2021;Granello & Gibbs, 2016). Our results in this area also link to other findings that suggest that mental illness is used most commonly by people with mental health problems (Fox et al, 2021). However, our study looks beyond assessing stigma levels in different terms and more broadly examines different reasonings provided for preferred or nonpreferred terms aside from stigma.…”
Section: Mental Illnesssupporting
confidence: 90%
See 2 more Smart Citations